Translation, Adaptation, and Validation of the L’Échelle d’Interactions Infirmière-Patient-23 for the Portuguese Culture: - Ribeiro Agostinho, Paula; Mendes Gaspar, Maria Filomena; Potra, Teresa (MDPI, 2021)
Nursing care is based on the interaction between nurse and patient. The L’Échelled’Interactions Infirmière-Patient-23 (EIIP-23) is used to evaluate and understand the perceptionof nurses about their interventions in the practice of care, to reach better health results. The presentstudy aims to validate the questionnaire EIIP-23 to Portuguese, evaluating its psychometric prop-erties. Methods: This is methodological research for the process of cross-cultural translation andadaptation. Results: The process of cross-cultural translation and adaptation were satisfactory. Thecommittee of experts reached an agreement of more than 90% in the first evaluation for all theitems. The internal consistency of the nurse-patient interaction scale 22-PT (NPIS-22-PT) was 0.864.Exploratory and confirmatory factor analyses were carried out in the NPIS-22-PT model, with threefactors. The results show that the final factorial solution presents acceptable goodness of fit indexesand adequate convergent validity. Conclusion: The translated version produced a good qualitypsychometric evaluation, and can be considered a valid, trustworthy, and useful instrument toevaluate the nurse-patient interactions in Portugal. It showed acceptable reliability and validity inpsychometric tests. In the context of nursing, the NPIS-22-PT is a relevant instrument
The Multidimensional Nature of Nursing Care
Keywords: enfermagem clínica; Avaliação de enfermagem; Estudos de validação; Propriedades psicometricas